(untitled) ("Journal "U". Economy. Management. Finance.", 2018)
In article the role of organizational structure – as main element of project management is considered. Organizational structure at project management defines an order of interaction of participants of the project and exchange of information with the external environment. Possibilities of organizational structure as factor of successful implementation of the project are given in article.